2016
DOI: 10.1002/asia.201501353
|View full text |Cite
|
Sign up to set email alerts
|

An Enantioselective Assembly of Dihydropyranones through an NHC/LiCl‐Mediated in situ Activation of α,β‐Unsaturated Carboxylic Acids

Abstract: A straightforward N-heterocyclic carbene (NHC)/LiCl-mediated synthesis of dihydropyranones from α,β-unsaturated carboxylic acids and 1,3-dicarbonyl compounds was realized through the in situ activation strategy. The key advantages of this protocol include ready availability and high stability of starting materials, good yields, and excellent enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 109 publications
1
6
0
1
Order By: Relevance
“…In the 13 C NMR spectrum, the resonance of imidazolium carbon (N C N) appears at 135.3 ppm. These values are consistent with those of reported imidazolium salts . The NHC‐PdCl 2 species was prepared via the reaction of compound 1 with PdCl 2 in the presence of base, and it was used in situ and not separated.…”
Section: Resultssupporting
confidence: 88%
“…In the 13 C NMR spectrum, the resonance of imidazolium carbon (N C N) appears at 135.3 ppm. These values are consistent with those of reported imidazolium salts . The NHC‐PdCl 2 species was prepared via the reaction of compound 1 with PdCl 2 in the presence of base, and it was used in situ and not separated.…”
Section: Resultssupporting
confidence: 88%
“…Next, we started to optimize the reaction conditions. It was reported that Lewis acids can be good cooperative catalysts in NHC catalysis due to the complexation of the O atom of the acylazolium ion with the metal cation, which should lower the LUMO and hence activate the Michael acceptor . Therefore, a series of Lewis acids were tested in this reaction, and LiCl was found to be the best, the ee value of 3a could be improved to 87%.…”
mentioning
confidence: 99%
“…The proton signal (NC H N) (δ = 9.59 ppm) for imidazolium in the 1 H NMR spectra of 2 was in line with the proton signals of known imidazolium salts. 19 , 20 Through referring to the literatures with structures similar to compound 2 , 21 , 22 we know that compound 2 is not an exactly symmetric structure, but the chemical environment of some protons is very close. Because the range of the 1 H NMR chemical shift is relatively small (0–10 ppm for Figure S11 ), some protons with a close chemical environment cannot be distinguished.…”
Section: Resultsmentioning
confidence: 99%